Dielectric ordering of water molecules arranged in a dipolar lattice - M. A. Belyanchikov (Nature Portfolio, 2020)
Despite the apparent simplicity of a H2O molecule, the mutual ferroelectric ordering of the molecules is unresolved. Here, the authors realize a macroscopic ferroelectric phase transition in a network of dipole-dipole coupled water molecules located in nanopores of gemstone.